Use of peer assessment in tooth extraction competency. (23rd May 2013) - Ali, K.; Heffernan, E.; Lambe, P.; Coombes, L.
Abstract Introduction Peer assessment is a widely recognised practice in higher education and is being increasingly utilised in healthcare education. It offers multiple advantages and may play a useful role in enhancing students' learning experience. This study was carried out to evaluate the utility of peer assessment in tooth extraction competency in simulated dental learning environment (SDLE). Methods Year 2 dental students were invited to participate in a formative, peer assessment exercise on forceps tooth extraction in SDLE. The ratings made by peers in the formative assessment were compared with the ratings made by academic supervisors in an equivalent summative assessment. Results One hundred and twenty‐two students participated in both the formative and summative assessments. Descriptive statistics demonstrated that the majority of students were given the same rating in both assessments. However, there were a number of students who were rated as 'Competent' in one assessment and 'Not Competent' in the other assessment. Spearman's Rho correlations showed that there were weak relationships between the formative and summative assessments. There was also weak inter‐rater reliability for the ratings of the peers and academic supervisors, as measured by the intraclass correlation coefficient. Feedback from the students and academic supervisors showed unanimously positive perceptions about the peer assessment experience, and they expressed the desire for incorporating peer assessment in other competencies. Conclusions This study shows mixed results with regard to the value of the peer assessment. Given the potential utility of peer assessment as a tool to augment and enrich students' learning experience, further work needs to be done to evaluate the use of peer assessment in operative competencies in dentistry.